Ultrasonic‐assisted exfoliation for 2D Zn(Bim)(OAc) nanosheets used as an oil‐soluble additive in lubricants. (2nd August 2020) - Wang, Fei‐Fei; Liu, Zan; Cheng, Zhi‐Lin
Abstract : The interface issue of two‐dimensional (2D) nanomaterials has seriously restricted their applications in the past. To date, there have been few reports on the friction behavior of 2D MOFs. Herein, 2D Zn(Bim)(OAc) metal–organic framework structure nanosheets with a thickness of ca. 4 nm were successfully prepared via convenient ultrasonic‐assisted exfoliation in solvents. For the first time, we probed the dispersion performance of the as‐obtained 2D Zn(Bim)(OAc) in different oils, and intensively investigated the tribological behavior. The results indicated that the as‐obtained 2D Zn(Bim)(OAc) used as an additive showed the preferable friction reducing performance and wear resistance in liquid paraffin, and showed the better dispersivity in glycerol. Abstract : The exfoliation schematic route of 3D bulk‐layered Zn(Bim)(OAc) into 2D MONs and their tribological properties.